Susret slovenskih prekmurskih i hrvatskih međimurskih govora - Lončarić, Mijo (Slavistična revija, 2007)
The study presents and connects some dialectal features, mainly phonological, of the peripheral idioms at the meeting point of two languages, i.e., Croatian Međimurje and Slovene Prekmuje dialects.
Keywords: Croatian language; glasoslovje; hrvaščina; Međimurje dialects; međimurski govori; phonology; Prekmuje dialects; prekmurski govori; Slovene language; slovenščina